The doctoral journey in music education: Reflections on doctoral studies by Australian music educators - Forrest, David (Australia Common ground, 2003)
This collection of reflections is the first time that a group of Australian music educators has reflected on their doctoral journey. The writers were asked to describe their doctoral journey, and comment on relevant academic, personal and other aspects relating to their journey. The reflections are exciting, informative and encouraging. They have been written with the knowledge that through these commentaries the journeys of others might be easier but, hopefully just as adventurous.